KAJIAN POTENSI SUMBERDAYA LAHAN SAWAH, PERMASALAHAN DAN PENGELOLAANNYA DALAM UPAYA PENINGKATAN PRODUKSI PADI DI SULAWESI TENGGARA - Asmin .; La Karimuna -; Suharno - (Agriplus, 2014)
Wet land is a sort of land which has a specific character of water availability as a long planting period.  Potency of wet land natural resources in Southeast Sulawesi province is high, where   wet land cropping system has been practiced for a long time by the farmers.  Rice productivity earned for the last ten years from 2004 to 2013 was still relativity low amounted to 2,667 - 4,225 t ha-1.  The objective of this paper was to study the potency of wet land used for rice cultivication, problems faced and management strategies to increase soil productivity for rice cultivication of Southeast Sulawesi province, through reference studies and description methods.  Based on the results of studies indicated that the main problems for increasing rice productivity in the study region were the shortage of using superior variety of rice, low level of soil fertility and discret of application technology based recommendation. In order to increase rice productivity of farming system, various strategies should be applied through the use of high potency of rice variety from the stock seed rice which released by source seed management unit (UPBS) classified as Foundation Seed (FS) and Stock Seed (SS) class; the application of appropriate wet land management through soil and water management, efficiency of fertilizer management (wise use of organic and inorganic fertilizers) and integrated nutrient management and crops in improving sustainable crop production.